Assessment workplace related factors affecting tolerance of ambiguity among trainee doctors - Inam, Shazia; Masood Jawaid; Rehan Ahmed Khan (Journal of the Pakistan Medical Association, 2023)
Objective: To assess workplace factors influencing the tolerance of ambiguity among trainee doctors. Methods: The sequential mixed-method study was conducted from June 2021 to February 2022 at the Fauji Foundation Hospital, Islamabad, Pakistan, and comprised postgraduate trainee doctors of either gender associated with various specialties. The baseline tolerance of ambiguity score was established using the Tolerance of Ambiguity in Medical Students and Doctors scale. A group of selected trainees was interviewed face-to-face to examine the workplace factors that they regarded as beneficial or detrimental to their tolerance of ambiguity. Quantitative data was analysed using SPSS 24 and thematic analysis was done for qualitative data. Results: Of the 132 subjects, 59 (21.9%) were males and 73 (55.3%) were females. The overall mean age was 20.95±2.186 years. Of the total, 55(41.7%) subjects were in the first year of training, 28(21.2%) in the second year, 26(19.6%) in the third year, and 23(17.4%) in the fourth year. There were 78(59.1%) trainees who were married compared to 54(40.9%) who were unmarried. Against the baseline tolerance of ambiguity score of 132, the overall aggregate mean tolerance of ambiguity level was 71.28 ± 5.81 showing a moderate level. There was no significant correlation between the tolerance of ambiguity and the trainees’ age, years of training and marital status (p>0.05). The qualitative phase comprised interviews with 9(6.8%) subjects. Thematic analysis suggested that the trainees perceived autonomy, peer support, supervisor support, manageable workload, and professional development opportunities as facilitators of tolerance of ambiguity, while barriers were identified as poor physical environment, attitude of seniors and supervisors, management issues and excessive workload. During the coronavirus diseae-2019 pandemic, excessive workload and fear of infection were identified as factors affecting tolerance of ambiguity. Conclusion: The medical trainees were found to have a moderate level of tolerance to ambiguity. Autonomy, peer support, supervisor support, manageable workload, and professional development opportunities contributed positively to this regard. Key Words: Clinical uncertainty, Clinical decision-making, Mental health, Workplace stress, Physicians.